New strategy to control covid-19 pandemic using lead/lag compensator. (July 2021) - Hadi, Musadaq A.; Amean, Zainab M.
Highlights: A new topic (COVID-19 pandemic) has been introduced in the literature of control theory. In addition, a new strategy (lead/lag compensator) been applied to the COVID-19 nonlinear. The data of the paper are valid for a certain period of time and the controller could be applied to the same system with different data. The stability of the system has been achieved and the system performance has been improved. Moreover, the parameters of the proposed controller have been optimized using new method called the Most Valuable Player Algorithm (MVPA). Abstract: COVID-19 is still the main worldwide issue since the outbreak. Many strategies were implemented such as suppression, mitigation, and mathematical-engineering strategies, to control this pandemic. In this work, a lead/lag compensator is proposed to control an unstable Covid-19 nonlinear system after using some required assumptions. The control theory is involved with the unstable pandemic and other existing strategies until the invention of the vaccine is approved. In addition, the Most Valuable Player Algorithm (MVPA) is used to optimize the parameters of the proposed controller and to determine whether it is a lead or lag compensator. Finally, the simulation results are based on the daily reports of two pandemic cities: Hubei (China), and Lazio (Italy) since the outbreak began. It can be concluded that the lead/lag compensator can effectively control the COVID-19 system.